Some Questions about the Slavic Tribes that participated in the Anti-Bulgarian Uprisings along the Mid-Danube in the First Decades of the 9th Century - Hrissimov, Nikolay (Studia Ceranea, 2022)
The article tries to answer three questions related to the tribes that came into conflict with the Bulgarian state during its expansion to the west in the first third of the 9th century. And the questions addressed in it are: 1. How many and which tribes were in conflict with the Bulgarian state?; 2. When were the lands of the Timociani annexed by the Bulgarian state?; 3. Where were the lands of the Abodriti-Praedenecenti and what caused the Bulgarian aggression towards them? After a thorough review and criticism of the sources and research on the issues under consideration, the following conclusions have been reached. From the beginning of the study of the problem how many tribes participated in the unrest against the Bulgarian state, P. Šafárik has the idea that among the tribes in the narrative sources, can be found other tribes as well. Thus appear the tribes of Bodriči (sounding, perhaps, like Krivichi), Kučani (Guduskani), Braničevci and others. After an assessment of the information in the Annales Regni Francorum, it turns out that the only tribes recorded in the source that had a clash with the Bulgarian state in the period were the Timociani and Abodriti-Praedenecenti. Since it is not directly related to the events that took place in 818, the question of when the Timociani lands were annexed to the Bulgarian state is hardly touched by the researchers. After research and exclusion of other possibilities, the thesis is defended that this could have happened recently after the Bulgarian conquest of Serdica in 809. With the inclusion of Serdica within the Bulgarian borders, Bulgaria controlled south of the Danube River not only the Danube plain but also the territories lying along the Thessaloniki-Danube axis. From this point on, the territories lying along this axis could be gradually taken over. Being further away from Byzantium, the lands located north of Sredets are more easily assimilated. It is in these territories that the Timociani fall. Given all the above, it can be assumed that it was after the capture and absorption of Sredets that the Bulgarian State looked northwest, but still south of the Danube river, where the Timociani lived. It seems that at this time an alliance was made with them, which turned out to be not particularly lasting. About the habitation of the Abodriti-Praedenecenti tribe in the information of 824, it is recorded that they lived in Danubian Dacia and were neighbours of the Bulgars. On the question of where this Dacia is located, which in its description does not correspond to any of the previously known Dacias, many hypotheses have been expressed, and in modern times most researchers are of the opinion that the lands of the Abodriti-Praedenecenti were located along the Left Bank of the river Danube, on the territory of modern Banat, i.e. east of the river Tisza. New evidence has been added to the localization of these habitations. In this case, the following question logically arises: provided that the Timociani lived on the Southern, Right Bank of the Danube, what caused the unfriendly relations of the Bulgarian state to the Abodriti-Praedenecenti living on the other side of the Big River? Given the size of the Danube River, it is quite difficult to cross and to transfer the fighting to the other bank of the Danube clearly should have had serious reasons. One of the possible explanations for this could be the transfer of the Timociani to their territory, on their way to the West, thus creating a casus belli for the Bulgars.